The Influence of Civil Servant Integrity, Internal Control Effectiveness and Accountability on Fraud Prevention in Sub-districts in Palembang City - Syaraveni Haravei; Sopiyan Ar; Rosy Armain (International Journal of Economics, Business and Innovation Research, 2026)
Fraud prevention is an integrated effort that can suppress and minimize the factors causing fraudulent acts. Forms of misappropriation or fraud committed intentionally to gain personal or group benefits will damage the order and finances of an organization and will eliminate public trust in the performance of state apparatus. The objectives of this study are (1) to examine the effect of Apparatus Integrity on fraud prevention, (2) to examine the effect of Internal Control Effectiveness on fraud prevention, and (3) to examine the effect of Accountability on fraud prevention. The type of research used is quantitative with a causal study approach. The sample in this study amounted to 86 people using a purposive sampling technique through questionnaire distribution. The data analysis method in this study is multiple linear regression using SPSS version 2.6 software. The results of this study indicate that partially the variables of apparatus integrity and internal control effectiveness have a positive and significant effect on fraud prevention. Meanwhile, the accountability variable does not affect fraud prevention carried out in sub-districts in the city of Palembang.